Theoretical principles and experimental data to identify stability of asphalt concrete components in finally dosed mineral materials - Sivilevičius, Henrikas (Transport, 2002)
The duration of asphalt concrete functioning depends on the quality of the asphalt concrete mixture used to pave the road. Grading of hot fractions sieved through technological sieves of asphalt concrete mixture, their pollution with particles of different size as well as stability influence on the quality of an asphalt concrete mixture. Each j – ( j = 1...., m) aggregate mineral material or mixture is made up of two (mineral powder, particle of size less than 0,09 or 0,071 mm, and sand, particle of size from 2 to 0,09 mm or 5-0,071 mm) or three (crushed stone, particle size is larger than 2 or 5 mm) mineral components (i = 1, ..., k) . When required technological operations of asphalt concrete mixture production are carried out, the quantity and stability of any i – component in mineral materials change when they move through an asphalt concrete mixer. The more stable the quantity of mineral components in mineral materials (especially in finally dosed) is, the more uniform the composition of asphalt concrete mixture is produced. The experiments showed that when asphalt concrete mixture is produced applying a traditional technology in an asphalt concrete mixer of model D-597, D-508-2A, D-645-3 and D-590, sieved hot fractions of 0–5 mm and 5–15 are polluted with particles of different size by more than 10 per cent; and this pollution is neither uniform nor stable. Following a well-known theory, an average quadratic deviation σ of arithmetic undersized particles sieved through laboratory sieves aggregate mineral materials is the greatest when their mean X makes up 50 per cent; therefore, hot fractions of 0–5 mm and 5–15 mm were produced on the experimental data obtained from production as well as regression equations σ = ƒ(X) of statistical indeces of cold mineral powder. The values of average quadratic deviations σ µij of mineral component quantities in those finally dosed mineral materials are obtained from curves drawn according to the regression equations. They can be used to estimate dispersion σ2Gi of mineral component i in asphalt concrete mixture which depends on the accuracy and stability of technological factors of an asphalt concrete mixer. Article in Lithuanian. Galutiniai dozuojamose mineralinėse medžiagose esančių asfaltbetonio komponentų stabilumo nustatymo teoriniai principai ir eksperimentiniai duomenys Santrauka. Atliktais eksperimentiniais tyrimais nustatyta, kad gaminant asfaltbetonio mišinį pagal klasikinę technologiją D-597, D-508-2A, D-645-3 ir D-590 modelio asfaltbetonio maišytuvuose, išsijotos karštosios 0–5 mm ir 5–15 mm frakcijos yra užterštos kitų matmenų grūdeliais daugiau kaip 10 % ir ši tarša nėra vienoda bei pastovi. Remiantis žinoma teorija, kad biriosios mineralinės medžiagos suminių išbirų per kontrolinius sietus vidutinis kvadratinis nuokrypis σ yra didžiausias, kai jų vidurkis X sudaro 50 %, iš gamyboje gautų eksperimentinių duomenų sudarytos 0–5 mm ir 5–15 mm karštosios frakcijos, taip pat šaltųjų mineralinių miltelių šių statistinių rodiklių regresijos lygtys σ = ƒ(X). Iš pagal regresijos lygtis nubraižytų kreivių gautos šiose galutiniai dozuojamose mineralinėse medžiagose esančių mineralinių komplektų kiekių vidutinių kvadratinių nuokrypių σ µij vertės. Jas galima panaudoti apskaičiuojant asfaltbetonio mišinio i-ojo mineralinio komponento kiekio dispersiją σ2Gi , priklausančią nuo jo gamybos asfaltbetonio maišytuve technologinių veiksnių tikslumo ir stabilumo. Raktažodžiai: asfaltbetonio mišinys, asfaltbetonio maišytuvas, karštosios frakcijos, sijojimo kokybė, granuliometrinės sudėties stabilumas, variaciją remiantis veiksniai. First Published Online: 19 Oct 2011